Gamma-Delta CAR-T Cells Show CAR-Directed and Independent Activity Against Leukemia - Rozenbaum, Meir; Meir, Amilia; Aharony, Yarden; Itzhaki, Orit; Schachter, Jacob; Bank, Ilan; Jacoby, Elad; Besser, Michal J. (Frontiers in Immunology, 2020)
Autologous T cells engineered to express a chimeric antigen receptor (CAR) against the CD19 antigen are in the frontline of contemporary hemato-oncology therapies, leading to high remission rates in B-cell malignancies. Although effective, major obstacles involve the complex and costly individualized manufacturing process, and CD19 target antigen loss or modulation leading to resistant and relapse following CAR therapy. A potential solution for these limitations is the use of donor-derived γδT cells as a CAR backbone. γδT cells lack allogenecity and are safely used in haploidentical transplants. Moreover, γδT cells are known to mediate natural anti-tumor responses. Here, we describe a 14-day production process initiated from peripheral-blood mononuclear cells, leading to a median 185-fold expansion of γδ T cells with high purity (>98% CD3+ and >99% γδTCR+). CAR transduction efficacy of γδ T cells was equally high when compared to standard CAR-T cells (60.5 ± 13.2% and 65.3 ± 18.3%, respectively). CD19-directed γδCAR-T cells were effective against CD19+ cell lines in vitro and in vivo, showing cytokine production, direct target killing, and clearance of bone marrow leukemic cells in an NSG model. Multiple injections of γδCAR-T cells and priming of mice with zoledronate lead to enhanced tumor reduction in vivo. Unlike standard CD19 CAR-T cells, γδCAR-T cells were able to target CD19 antigen negative leukemia cells, an effect that was enhanced after priming the cells with zoledronate. In conclusion, γδCAR-T cell production is feasible and leads to highly pure and efficient effector cells. γδCAR-T cell may provide a promising platform in the allogeneic setting, and may target leukemic cells also after antigen loss.